Sensitivity Pattern of Uropathogens in Diabetic and Non-Diabetic Patients Presenting to a Tertiary Care Hospital: Uropathogen Sensitivity in Diabetic Patients - Nisar, Muhammad; Farooq, Muhammad Waqar; Asadullah; Ahmad, Nisar (Pakistan Journal of Health Sciences, 2024)
Diabetes Mellitus (DM) is a prevalent global health issue, with Pakistan experiencing a high burden. Diabetic patients were more susceptible to Urinary Tract Infections (UTIs) and often exhibit greater antibiotic resistance. Objective: To determine the sensitivity/resistance patterns of DM and Non-DM UTI patients. Methods: A cross-sectional study was conducted on 208-UTI at Lady Reading Hospital, Peshawar, from January to July 2020. Patients were equally divided into DM (n=104) and non-DM (n=104) groups. Results: A total of 208 UTI cases were equally divided between diabetic and non-diabetic groups (104 in each). The mean age of patients was 42.49 ± 1.148 years with a male predominance 132 (63.4%). Dysuria was reported in 81 (38.9%), urinary frequency in 86 (41.3%), and fever in 41 (19.7%) patients. Significant differences were observed in antibiotic resistance patterns between diabetic and non-diabetic groups. Diabetic patients exhibited higher resistance to Meropenem 86 (78%) versus 24 (22%), p<0.001), Ciprofloxacin 95 (98%) versus 2 (2%), p<0.001), and Ceftazidime 93 (79.4%) versus 24(20.6%), p<0.001) compared to non-diabetics. Conversely, sensitivity were significantly lower in diabetic patients for Meropenem (18(18%) versus 80(82%), p<0.001), Ciprofloxacin (9(8%) versus 102(91.8%), p<0.001), and Ceftazidime (11(12.3%) versus 79(87.7%), p<0.001). No significant associations were found between age or gender and antibiotic sensitivity within either group. Conclusion: The study demonstrates that diabetic patients were at significantly higher risk for antibiotic-resistant UTIs, particularly against meropenem, ciprofloxacin, and ceftazidime. These findings highlight the importance of customized antibiotic therapies and better glycemic control in diabetic patients to reduce UTIs complications.